2018
DOI: 10.1002/jcph.1149
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Oral Propranolol in Pediatric Patients With Infantile Hemangioma

Abstract: This study aimed to characterize the population pharmacokinetics and exposure‐response relationship of propranolol (Hemangiol® Syrup for Pediatric) in infants with infantile hemangioma. Using nonlinear mixed‐effects modeling with 63 pooled sets of plasma concentration‐time data from 32 Japanese patients aged 35‐150 days, we described the disposition of propranolol adequately by a 1‐compartment model with first‐order absorption. The estimated population mean apparent clearance and apparent central volume of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…Of note, SAEs occurred in two prematurely born children, who may be more prone to hypoglycaemia and bronchial hyperreactivity as previously reported 32 . Therefore, low dose of Hemangiol(r) (2mg/kg/day) could be of interest in such high-risk children 23,28 , however the dosage of 3mg/kg/day has been more investigated in pharmacokinetics and pharmacodynamics studies 33,34 based on the manufacturer's clinical trial 18 . For all SAEs, causality scores concluded to possible to strong relation to Hemangiol(r).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, SAEs occurred in two prematurely born children, who may be more prone to hypoglycaemia and bronchial hyperreactivity as previously reported 32 . Therefore, low dose of Hemangiol(r) (2mg/kg/day) could be of interest in such high-risk children 23,28 , however the dosage of 3mg/kg/day has been more investigated in pharmacokinetics and pharmacodynamics studies 33,34 based on the manufacturer's clinical trial 18 . For all SAEs, causality scores concluded to possible to strong relation to Hemangiol(r).…”
Section: Discussionmentioning
confidence: 99%
“…The cream was shown to be safe with no serious side effects such as hypotension, bradycardia, or hypoglycemia, unlike the oral formulation. In a clinical study of an oral liquid formulation in Japanese subjects, the median simulated trough concentrations in the plasma after repeated oral administration of 3 mg/kg/day propranolol twice daily for 168 h were 16.7, 20.8, and 26.4 ng/mL at 6, 9, and 12 h, respectively [9]. In the present study, plasma concentrations were measured at weeks 4 and 24; both of the highest values were considerably lower than the simulated trough concentration, suggesting that the drug had little systemic effect and was only locally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two separate pharmacokinetic studies demonstrated that irregular twice daily dosing with as short as a 6hour interval does not affect propranolol's efficacy. 11,12 In fact, this is probably the stronger conclusion I would derive from the study.…”
mentioning
confidence: 86%
“…If given in the early afternoon, less propranolol will be in the blood stream at night, potentially causing less sleep disturbance. Moreover, two separate pharmacokinetic studies demonstrated that irregular twice daily dosing with as short as a 6‐hour interval does not affect propranolol's efficacy 11,12 . In fact, this is probably the stronger conclusion I would derive from the study.…”
mentioning
confidence: 96%